Optimization of biogas production through co-digestion of cafeteria food waste and cow dung using the response surface methodology - Bidiko, Gezahegn Batebo; Sangib, Elyas Belay; Gnaro, Mikiyas Abewaa (Frontiers in Energy Research, 2025)
Biogas, a renewable energy, is produced by the anaerobic digestion of organic materials into methane-rich combustible gas. In this context, this study evaluated biogas production from cafeteria food waste (CFW) and cow dung (CD) via co-digestion under mesophilic conditions using a batch digester. To assess the effectiveness of the process, key physicochemical parameters, including total solids, volatile solids, moisture content, carbon-to-nitrogen ratio, and pH, were determined before and after digestion. Furthermore, optimization of biogas production was performed using the response surface methodology with a three-factor, three-level Box–Behnken design to analyze the effects of CFW-to-CD ratio, pH, and temperature. Accordingly, 17 experimental runs were conducted in triplicate, and the optimal conditions were determined to be a CFW-to-CD ratio of 3, pH 7.0°C, and 37.5°C, which resulted in the maximum biogas yield of 197 mL with 62.5% methane. These findings suggest that co-digestion of CFW and CD holds significant potential for enhancing the biogas yield and methane composition. Therefore, this approach offers an efficient and sustainable solution for renewable energy production, effectively transforming organic waste into a beneficial energy resource.